Pembrolizumab Alone or Combined With Chemotherapy in Advanced NSCLC With PD-L1 ≥50%: Results of a Retrospective Study - Chen, Ya; Wang, Yanan; Yang, Zhengyu; Hu, Minjuan; Zhang, Yanwei; Qian, Fangfei; Zhang, Wei; Zhang, Bo; Han, Baohui (Frontiers in Oncology, 2021)
Objectives: Pembrolizumab plus platinum-based chemotherapy and pembrolizumab monotherapy (PM) both become standard of care in patients with advanced non-small-cell lung cancer (NSCLC) and a programmed death ligand 1 (PD-L1) tumor proportion score (TPS) greater than 50%. This study aimed to figure out the better treatment choice. Materials and Methods: In this retrospective analysis, we compared the clinical efficacy of PM and PC as first-line treatment in NSCLC patients with a PD-L1 ≥50% and negative for genomic alterations in the EGFR and ALK genes. Results: Among the population, 115 patients received PC and 91 patients received PM. Up to Dec 30, 2020, median follow-up was 17.13 months. The median progression-free survival (PFS) of PC and PM were 12.37 and 9.60 months (HR:0.44, p <0.001), respectively. The median overall survival (OS) were NE and 28.91 months (HR:0.40, p =0.008), respectively. Subgroup analysis found that the PFS benefit of PC was evident in most subgroups excepting patients with brain metastasis. The 1-year overall survival rate of PC and PM were 89.0% and 78.3%, respectively. The ORR were 61.7% and 46.9% (p=0.040), respectively. Conclusion: In patients with previously untreated, PD-L1≥50%, advanced NSCLC without EGFR or ALK mutations, the addition of pembrolizumab to standard platinum-based chemotherapy should be recommended as the preferred treatment.